Design of thiazole orange oligonucleotide probes for detection of DNA and RNA by fluorescence and duplex melting - Klimkowski, Piotr (Royal Society of Chemistry, 2019)

(untitled) (Org Biomol Chem)
We have synthesised a range of thiazole orange (TO) functionalised oligonucleotides for nucleic acid detection in which TO is attached to the nucleobase or sugar of thymidine. The properties of duplexes between TO-probes and their DNA and RNA targets strongly depend on the length of the linker between TO and the oligonucleotide, the position of attachment of TO to the nucleotide (major or minor groove) and the mode of attachment of thiazole orange (via benzothiazole or quinoline moiety). This information can be used to design probes for detection of target nucleic acids by fluorescence or duplex melting. With cellular imaging in mind we show that 2′-OMe RNA probes with TO at the 5-position of uracil or the 2′-position of the ribose sugar are particularly effective, exhibiting up to 44-fold fluorescence enhancement against DNA and RNA, and high duplex stability. Excellent mismatch discrimination is achieved when the mispaired base is located adjacent to the TO-modified nucleotide rather than opposite to it. The simple design, ease of synthesis and favourable properties of these TO probes suggest applications in fluorescent imaging of DNA and RNA in a cellular context.